Dinamika Kebijakan Program Kredit Usaha Rakyat (KUR) di Indonesia - Eko Aristanto; Umu Khouroh; Christina Sri Ratnaningsih (Jurnal Manajemen dan Kewirausahaan, 2020)
This study aims to: 1) analyze the development of regulations, governance and the Kredit Usaha Rakyat scheme; 2) analyzes interest subsidy policies in the Kredit Usaha Rakyat Program; and 3) analyze the development and performance of the distribution of the Kredit Usaha Rakyat Program. This type of research used associative descriptive research with research indicators are regulations, interest rates, realization and debtors on the distribution of the Kredit Usaha Rakyat Program. The research period is conducted from 2008 to 2019 with observations on banks channeling Kredit Usaha Rakyat Program. The results of the study explained that during the period 2008 to 2019 there were 37 regulations governing the governance of the Kredit Usaha Rakyat Program, there was a change in management from a credit guarantee scheme to an interest subsidy scheme that had an impact on reducing interest rates, increasing the realization of the distribution and debtors of the Kredit Usaha Rakyat.https://doi.org/10.26905/jmdk.v8i1.4247